Inclusive education in South Africa and the developing world : the search for an inclusive pedagogy - Naicker, Sigamoney Manicka (Emerald points., 2018)
This book offers a framework for the implementation ofinclusive education in developing countries. It proposes bringing the vulnerable to the centre of planning decisions, recognising the history of special education inpsychologizing failure, and that mainstream must own the transformation to inclusive education.